Analisis strategi pengembangan karyawan dalam meningkatkan kualitas kinerja perbankan - Aprelia, Nala Widya (Maliki Interdisciplinary Journal, 2024)
This research examines the strategies needed in conducting employee training and development to improve the quality of banking performance. In improving banking performance, companies need to analyse what strategies can be done to achieve these goals. One of them is to conduct training and development for employees. The approach chosen in this research is descriptive qualitative with data taken from the last 10 years. This research explains the purpose of implementing training and development to improve the quality of banking performance. There is an analysis done as a first step and several strategies that can be implemented. With the training and development will have an impact on the quality of employees, customers, and banking itself. Qualified employees, customer satisfaction and increased productivity that affects the quality of banking performance.